Weekend admissions and outcomes in patients with pneumonia: a systematic review and meta-analysis - Lu, Jiayao; Yang, Jing; Cai, Xiaofei (Frontiers in Public Health, 2024)
Background To document pooled evidence on the association between weekend hospital admissions and the potential risks of mortality, intensive care requirements, and readmission among patients with pneumonia. Methods We performed a systematic search across the PubMed, EMBASE, and Scopus databases. We collected observational studies exploring the association between weekend admissions and outcomes of interest in patients with pneumonia. To analyze the data, we used a random effects model and expressed the effect sizes as pooled odds ratios (ORs) accompanied by their respective 95% confidence intervals (CIs). Results The analysis comprised data from 13 retrospective studies. Compared to patients admitted on weekdays, those admitted during the weekend had a non-statistically significant marginally higher risk of in-hospital mortality (OR, 1.02; 95% CI, 1.00, 1.04) but similar 30-day mortality after admission (OR, 1.03; 95% CI, 0.97, 1.10), and similar risks of admission to intensive care unit (OR, 1.04; 95% CI, 0.98, 1.11) and re-admission (OR, 0.85; 95% CI, 0.65–1.12). Conclusion Our findings do not support the presence of a “weekend effect” in patients with pneumonia. Systematic review registration PROSPERO, identifier CRD42023425802, https://www.crd.york.ac.uk/prospero/.